KEBIASAAN MENCUCI TANGAN PADA ANAK SEKOLAH DENGAN KEJADIAN KECACINGAN DI DAERAH PESISIR DESA TADUI KECAMATAN MAMUJU - Rahmat Haji Saeni; Erdiawati Arief (Jurnal Kesehatan Manarang, 2017)
The World Health Organization (WHO) in 2011 estimates that more than 2 billion people are infected with worms around the world, about 300 million suffer from severe worm infections and about 150,000 deaths occur annually due to STI (Soil transmitted helminths) infections. Deworming has a major impact on society because it affects intake, digestion, absorption and food metabolism. Cumulatively worm infections can cause nutritional loss of calories and proteins and blood loss that can cause anemia, inhibit physical development, mental, intellectual decline in children and work productivity, can decrease the body's resistance so easily affected by other diseases. The purpose of this study was to determine the relationship between hand washing habits and bathing habits with the incidence of worms. The research method used is cross sectional. The results of this study showed that there was a relationship between hand washing before eating and hand washing after to the occurrence of worm infestation with p value of 0.02 and 0.04 respectively. The relationship of bathing habits also showed a statistical relationship with a p value of 0.03, whereas there was feces in the nails also showed a statistical relationship with a p value of 0.00. Conducting efforts to promote clean and good living behavior both at school and community. Improve the promotion of handwashing, especially handwashing with soap.